Influence of selected chemical properties in peat soils and mineral soils on BRIX content of pineapple variety MD2 / Mohd Firdaus Khairuddin - Khairuddin, Mohd Firdaus (Faculty of Plantation and Agrotechnology, 2018)
This study aims to relate the influences of selected chemical properties of peat soil and mineral soil on BRIX content of pineapple variety MD2. In this study, the soil samples and pineapple fruit samples were collected from two different locations. The samples were collected at Ayer Baloi for peat soil and mineral soil conducted, was obtained from Ayer Hitam, Johor. The fruit samples analysed for BRIX content of pineapple MD2 and soil sample were undergo the chemical properties analysis to determine the soil pH, Potassium, Phosphorus, Calcium, Magnesium, Aluminium and Iron availability. Results showed that the BRIX content is higher in mineral soil compared to the peat soil. This reflects to the higher nutrient content in mineral soil compared to the peat soils as a result of good soil pH.